William Shakespeare's A midsummer night's dream - Conner, Daniel; Espinosa, Rod; Shakespeare, William 1564-1616. (Edina, Minn. : Magic Wagon, 2009)
Retells, in comic book format, Shakespeare's play about the strange events that take place in a forest inhabited by fairies who magically transform the romantic fate of two young couples.
Keywords: Shakespeare, William -- 1564-1616; Courtship; Fairy plays; Fairies; Athens (Greece); Comedies; Youths' writings; Cartoons and comics; Graphic novels; Comedies; Graphic novels